The Switch from Ferric Gluconate to Ferric Carboxymaltose in Hemodialysis Patients Acts on Iron Metabolism, Erythropoietin, and Costs: A Retrospective Analysis - Antonio Lacquaniti; Romana Gargano; Susanna Campo; Teresa Casuscelli di Tocco; Silvia Schifilliti; Paolo Monardo (Medicina, 2023)
Background and Objectives: Iron deficiency and anemia characterize patients on chronic hemodialysis (HD). Available intravenous iron agents, such as ferric gluconate (FG) and ferric carboxymaltose (FCM), vary in dosing regimens and safety profiles. The aim of the present study was to analyze the modification of the iron status, the correction of anemia, and the economic implications after the shift from FG to FCM therapy in chronic HD patients. We evaluated, during the study, the variations in iron metabolism, assessing ferritin and transferrin saturation, erythropoietin-stimulating agent (ESA) doses and the number of administrations, the effects on anemic status, and consequent costs. Materials and Methods: A retrospective study was performed with a follow-up period of 24 months, enrolling forty-two HD patients. The enrolment phase started in January 2015, when patients were treated with iv FG, and continued until December 2015, when FG was discontinued, and, after a wash-out period, the same patients were treated with FCM. Results: The iron switch reduced the administered dose of ESA by 1610.500 UI (31% of reduction; p < 0.001) during the entire study period and reduced the erythropoietin resistance index (ERI) (10.1 ± 0.4 vs. 14.8 ± 0.5; p < 0.0001). The FCM group had the highest percentage of patients who did not require ESA treatment during the study period. The FCM patients were characterized by higher levels of iron (p = 0.04), ferritin (p < 0.001), and TSAT levels (p < 0.001) compared to the FG patients. The annual cost during FG infusion was estimated at EUR 105,390.2, while one year of treatment with FCM had a total cost of EUR 84,180.7 (a difference of EUR 21,209.51 (20%), saving EUR 42.1 per patient/month (p < 0.0001). Conclusions: FCM was a more effective treatment option than FG, reducing ESA dose requirements, increasing Hb levels, and improving iron status. The reduced ESA doses and the decreased number of patients needing ESA were the main factors for reducing overall costs.